Nuclear Receptors Current Concepts and Future Challenges - Bunce, Chris M.; Campbell, Moray J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
In 1890 a case of myxedema was treated in Lisbon by the implantation of a sheep thyroid gland with the immediate improvement in the patient$1 (Bs condition. A few years later, medications for the then ill-explained condition of the menopause included tablets made from cow ovaries. In the first quarter of the 20th century the identification of vitamin D, and its sunlight driven production in skin, paved the way to the elimination of rickets as a major medical problem. Twenty years or so later, Sir Vincent Wigglesworth established the endocrine basis of developmental moulting in insects, arguably the most commonly performed animal behaviour on Planet Earth. A paradigm that would unify these disparate observations arose between 1985 and 1987 beginning with the identification of the glucocorticoid receptor and the nuclear receptor super-family. What follows is a timely and positive manifestation of the capacity, productivity and value of international human scientific endeavour. Based on intrigue, lively competition and cooperation a global effort has rapidly fostered a school of biology with widespread ramifications for the understanding of metazoan animals, the human condition and the state of the planet. This book is the first this century to try and capture the spirit of this endeavour, to depict where the field is now and to identify some of the challenges and opportunities for the future.s
Nuclear Receptors an Introductory Overview -- What does Evolution Teach us about Nuclear Receptors? -- Functions of Nuclear Receptors in Insect Development -- The Glucocorticoid Receptor -- Estrogen Receptors: Their Actions and Functional Roles in Health and Disease -- Androgen Receptor -- Thyroid Hormone Receptors -- The Vitamin D Receptor (NR1I1) -- Retinoic Acid Receptors -- PPARs: Important Regulators in Metabolism and Inflammation -- Xenobiotic Receptors CAR and PXR -- Fxr -- Physiological Functions of TR2 and TR4 Orphan Nuclear Receptor -- Nuclear Receptors and ATP Dependent Chromatin Remodeling: A Complex Story -- Non-Genomic Action of Sex Steroid Hormones -- Ligand Regulation and Nuclear Receptor Action -- New Insights to Nuclear Receptor Gene Regulation from Analysis of their Response Elements in Target Genes -- Systems Biology: Towards Realistic and Useful Models of Molecular Networks.
Keywords: Medicine; Endocrinology; Oncology; Biochemistry; Cytology; Biomedicine; Biomedicine general; Cell Biology; Endocrinology; Animal Biochemistry; Oncology